ARTISTA PATY WOLFF - CONTRIBUIÇÃO PARA EDUCAÇÃO DAS RELAÇÕES ÉTNICO-RACIAIS DE ESTUDANTES DA EDUCAÇÃO BÁSICA - JULIANA FERREIRA DE ALMEIDA (2024)
This research is focused on education regarding ethnic-racial relations through the teaching of art as an instrument of representation and appreciation of African culture. The development of didactic classes is proposed, covering the teaching of Afro-Brazilian history and culture, in accordance with laws nº 10.639/03 and nº 11.645/08 that made the teaching of Afro-Brazilian culture mandatory, with the aim of promoting social principles multicultural and legitimately democratic, associated with confronting racism in the school space. Seeking to involve students in the debate on the construction of social identities, multiculturalism, ethnic diversities, racism and African culture. The proposed pedagogical intervention was developed at EMEB José Torquato da Silva (Cuiabá/MT), with the 4th year C class - considered a multiethnic class - and was built from a theoretical reflection around decolonial thinking with a dialogue with following authors: Eliane Cavalleiro (2001 and 2003), Djamila Ribeiro (2019) and bell hooks (2017), women who contextualize the racism present in education. This intervention is based on the works of Cuiabana artist Paty Wolff, who, through paintings, sculptures and illustrations from her book Como Aves no Céu de Aruanda (Entrelinhas, 2021), works on the representation and look at the bodies of black people. (to the).